Unequal Time : Gender, Class, and Family in Employment Schedules - Clawson, Dan (Book collections on Project MUSE., 2014)
"Unequal Time investigates the connected schedules of four health sector occupations: professional doctors and nurses, and working-class EMTs and nursing assistants. While the work-family literature mostly examines the hours people work, Clawson and Gerstel delve into the process through which schedules are set, negotiated, and contested. They show how workers in all four occupations experience the effects of schedule uncertainty but do so in distinct ways, largely shaped by the intersection of gender and class. Doctors, who are largely male and professional, have significant control over their schedules, though they often claim otherwise, and tend to work long hours because they earn respect from their peers for doing so. By contrast, nursing assistants, primarily female and working-class, work demanding hours because they face penalties for taking time off, no matter how valid the reasons. Without institutional support, they often turn to coworkers to help create more orderly lives."--Publisher's Web site